Spectrum of MRI findings in traumaticknee - Kaur Mohi, Jaswinder; Bhatnagar, Simmi; Kaur, Navkiran; Bansal, Neha (International Journal of Medical Research and Review, 2018)
Introduction: Injuries to the intraarticular structures like menisci and cruciate ligame nts are diagnosed with high sensitivity and specificity by MRI as compared with arthroscopy, which is still regarded as the gold standard. The acutely injured knee is readily imaged for the detection of meniscal and ligamentous injuries. Aim: To describe the MRI features in various types of traumatic lesions andto analyze the types of knee joint abnormalities detected by MRI which will aid in making a proper diagnosis. Materials and Methods: A total of 51 patients with history of trauma to the knee joint, who were referred to radiology department from orthopaedic department of Rajindra hospital Patiala, suspecting internal derangement of knee, served as subjects for this study. The inclusion and exclusion criteriafor this study was fixed as well as MRI protocol which included T1 and T2 saggital, PD weighted sequences in axial, Coronal and Saggital, Fat Suppressed T2 or STIR sequences if needed. The different types of lesions of all components of knee joint were categorized separately and data was assessed. Results: Out of 51 patients who underwent MRI with history of trauma, 23 (45%) patients had abnormal ACL and 28 (54.9%) patients had normal ACL. PCL was found abnormal in only 3 (5.8%) patients. MCL was abnormal in 5 (9.8%), joint effusion was seen in maximum no of 44 (86.2%) patients. Muscular pathology was seen in 1patient and bone pathology in 23 (45%) patients. In medial meniscus tearsand lateral meniscus tears, posterior horn tears were the commonest. In ACL tears, acute partial tears were the commonest (61%). Conclusion: In the setting of traumatic knee injury, MR imaging is the best noninvasive modality for the diagnosis of meniscal and ligamentous tears and to help guide the treatment of meniscal and ligament injuries.